The association between serum testosterone levels and cognitive function of men aged 50 years or more (Faculty of Medicine Universitas Indonesia, 2009)
Aim The Aging process is a major risk factor for the development of degenerative diseases, including cognitive impairment. Many studies have shown that reduced cognitive function is associated with low testosterone levels. This study was aimed to know the association between serum testosterone level and cognitive functions in men who showed mild cognitive impairment. Method This was a cross-sectional study in men aged 50 years or more in Neuroscience Clinic Siloam Hospitals, Lippo Karawaci, Tangerang between 2002 and 2004. Subjects were patients who complained of decreasing cognitive function. Cognitive function was assessed by using the 30-point Mini-Mental State Examination (MMSE) questionnaires. Testosterone level was measured by using the enzyme-linked fluorescent assay (ELFA) method. Results A total of 112 men were recruited during the study period. The median age was 64 years old. One-hundred and one subjects underwent cognitive function test and serum testosterone assay. The mean MMSE score was 26 + 3.2 points, whereas the mean testosterone level was 14.7 + 5.72 nmol/L. Conclusion There was no significant correlation between the MMSE score and testosterone level (r=0,038). This study showed that men aged 50 years and above with symptoms of declined cognitive function have decreasing MMSE scores but were still within the normal range of testosterone levels. No correlation was found between MMSE scores and testosterone levels since most subjects were eugonadal. (Med J Indones 2009; 18: 36-40) Keywords: Testosterone, Cognitive function